Analysis of the parameters determining the effect of coated and uncoated papers on print quality - SESLİ, YASEMİN; AKGÜL, AHMET; OKTAV, MEHMET (My University, 2023)
Both paper and ink are the two main raw materials in the manufacture of printed materials. The visual quality of the printed product is very important. Printing an image on paper with ink in high resolution is dependent on the quality of the interfacial relationship between paper and ink. Newsprint, book paper, and pure cellulose-based high-grade paper pulp where the mechanical wood pulp is intensively utilized have porous structures. Coldset offset printing is used for printing on these papers. The coldset offset printing is a printing process where drying occurs late by evaporation of the liquid portion of the ink and absorption into the paper. The ink can sometimes take several days to dry completely (solidify). During this drying process, the ink penetrates the cellulose capillaries in the paper in the vertical direction and behaves the same in the horizontal direction. The dot diameter, which mechanically grows due to the printing pressure (dot gain), grows even larger by spontaneous micro-steps during the drying process. It tends to cross to the back surface of the paper in a vertical direction. For this reason, the paper-ink interfacial behavior is a critical parameter that should be maintained under control as much as possible. The rough surface, porous structure and humidity of the paper, the viscosity and amount of ink printed on the paper surface, the printing pressure at the NIP point, and the physical conditions of the printing room are influential in this interfacial relationship. In this study, the factors that affect the image quality in printing on uncoated and coated papers were investigated by test printing. The CMYK test scale, which was specially prepared for the examination of print quality, was printed with Coldset Offset Printing on smooth papers coated with woodfree coated paper and woodfree uncoated paper, which are the best examples of uncoated papers and are widely used especially in book production. After printing, the surface of the papers was measured with a spectrophotometer and the dot growth and trapping values were determined. Surface and interfacial images of the prints were taken with a stereoscopic microscope and visual examinations were undertaken.

Kağıt ve mürekkep basılı malzeme üretiminde temel iki hammaddedir. Basılı mamül üzerinde görsel kalite çok önemlidir. Kağıt üzerinde, mürekkeple bir görüntüyü aslına uygun ve yüksek çözünürlükte basabilmek; kağıt ve mürekkep arayüzey ilişkisinin kalitesine bağlıdır. Mekanik odun hamurunun yoğun olarak kullanıldığı gazete kağıdı, kitap kağıdı ve saf selüloz esaslı 1.hamur kağıtlar gözenekli porozit yapıdadırlar. Bu kağıtlar üzerine baskı Coldset Ofset baskı ile gerçekleştirilir. Coldset ofset baskı, mürekkebin sıvı kısmının buharlaşması ve kağıda emilmesi yoluyla kurumanın geç gerçekleştiği bir baskı işlemidir. Mürekkebin tamamen kuruması (katılaşması) bazen birkaç gün sürebilir. Bu kuruma sürecinde kağıt bünyesindeki selüloz kapilerlerine dikey yönde nüfuz eden mürekkep, yatay yönde de aynı davranışı gösterir. Baskı basıncı nedeniyle mekanik olarak büyüyen (Dot Gain) nokta çapı kuruma sürecindeki kendiliğinden mikro adımlarla ilerleyerek daha da büyür. Dikey yönde ise kağıdın arka yüzeyine geçme eğilimindedir. Bu nedenle kağıt-mürekkep arayüzey davranışı mümkün olduğunca kontrol altında tutulması gereken önemli bir parametredir. Kağıdın pürüzlü yüzeyi, gözenekli yapısı ve nemi, mürekkebin viskozitesi ve kağıt yüzeyine basılan miktarı, NIP noktasındaki baskı basıncı, baskı odasının fiziksel şartları bu ara yüzey ilişkisinde etkilidir. Çalışmada yüzeyi kaplanmış ve kaplanmamış kağıtların üzerine baskıda görüntü kalitesine etki eden faktörler test baskısı yapılarak incelenmiştir. Baskı kalitesinin incelenmesi için özel hazırlanan CMYK test skalası, yüzeyi kaplanmamış kağıtlara en iyi örnek olan ve özellikle kitap üretiminde yoğun olarak kullanılan woodfree coated paper ve woodfree uncoated paper ile yüzeyi kaplanmış pürüzsüz kağıtlara, Coldset Ofset Baskı ile baskılar yapılmıştır. Baskı sonrası kağıtların yüzeyi spektrofotometre ile ölçülerek; nokta büyümeleri ve trapping değerleri tespit edilmiştir. Stereoskopik mikroskopla da baskıların yüzey ve arayüzey görüntüleri alınarak görsel incelemeler yapılmıştır.
Kaplanmış ve kaplanmamış kağıtların baskı kalitesine etkisini belirleyen parametrelerin analizi
Keywords: Coldset offset; Coated paper; Uncoated paper; Printability; Ofset baskı; Kaplanmış kağıt; Kaplanmamış kağıt; Basılabilirlik